Impact of thermal treatments on the bioaccessibility of phytoene and phytofluene in relation to changes in the microstructure and size of orange juice particles. (July 2018) - Mapelli-Brahm, Paula; Stinco, Carla M.; Rodrigo, María J.; Zacarías, Lorenzo; Meléndez-Martínez, Antonio J.
Graphical abstract: Highlights: Phytoene, phytofluene (PTF) and ζ-carotene behave similarly to thermal treatments. Phytoene and PTF have higher bioaccessibility than some carotenes and xanthophylls. TEM images show great disruptions of cell structures with the thermal treatments. Pasteurized juices have higher carotenoid bioaccessibility than frozen/thawed juices. Abstract: The interest in phytoene and phytofluene is expanding. In this study their bioaccessibility from thermally treated orange juices was analysed. Other carotenoids were also considered for comparison. Fresh, pasteurized, and ultrafrozen juices thawed at room temperature (UF-RT), in microwave oven (UF-MW), and in fridge (UF-FG) were investigated. Colourless carotenoids suffered less degradation as a result of ultrafreezing than xanthophylls. The carotenoid with highest bioaccessibility in the fresh juice was phytoene (10%). Total carotenoid bioaccessibility followed the order: Pasteurized > UF-MW > UF-RT > UF-FG > Fresh. The cells degradation followed this same order while the particle size followed the opposite, i.e. the samples with the higher bioaccessibility were those with lower particle size. Thus, it was concluded that thermal treatments could enhance the release of carotenoids from the matrix due to the degradation of cells which could explain the higher bioaccessibility. The best source of bioaccessible colourless carotenoids was UF-MW.